Impact of Chlorella sorokiniana feed additive on poultry growth health and oxidative stress in erythrocytes - Ioannis Tsamesidis; Anastasia Pappa; Aggelos Charisis; Zoi Prentza; Konstantinos Theocharis; Apostolos Patsias; Dimitrios Foukas; Christos Chatzidoukas; Eleni P. Kalogianni (Scientific Reports)
Abstract Microalgae, have emerged as a potentially promising feed additive option due to their beneficial nutritional profile rich in bioactive compounds. The present study examines the incorporation of Chlorella sorokiniana (at 0.1% and 1%) into chicken feed compared to control feed and its effect on growth and health parameters of poultry grown at pilot plant scale. Growth performance parameters (weight, feed conversion ratio (FCR), mortality, European Production Efficiency Index (EPEF)) and the immune system response are examined. In addition, it examines well-being gut health and nutrient absorption related variables via macroscopical and histological analysis. Finally, red blood cell (RBC) morphology and oxidative stress parameters (reactive oxygens species (ROS) and malondialdehyde level) in the whole blood as well as the lipid profile of the adipose tissue are determined. Addition of Chlorella sorokiniana at 0.1% resulted improved growth performance parameters whereas the ROS levels were significantly decreased indicating reduced oxidative stress. Finally, the results of histological analyses of the intestine on parameters related to nutrient absorption correlated with the results on growth performance. On the other hand, addition Chlorella sorokiniana at 1% did not affect significantly the growth performance parameters, resulted in increased footpad dermatitis, increased oxidative stress and alterations in RBC.